PEMBERIAN LATIHAN STABILISASI PADA TERAPI DASAR MICRO WAVE DIATHERMY LEBIH EFEKTIF UNTUK MENGURANGI NYERI DARIPADA WILLIAM FLEXION PADA TERAPI DASAR MICRO WAVE DIATHERMY PADA PASIEN SPONDYLOARTHROSIS LUMBAL - Purba, Jhon Roby; Tirtayasa, Ketut; Lesmana, S. Indra; Muliarta, Made; Sutjana, I D P; Irfan, Muh. (Sport and Fitness Journal, 2017)
Background: Spondyloarthtrosis lumbal is a kind of low back pain which caused by degeneration of discus, facet joint on lumbal. This degeneration causes a pressure on foramen invertebralis that causes tissue inflammation or it also caused because the spasm muscle that will causes ischemic, and at last ischemic causes pain. To decrease pain in spondyloarthrosis lumbal patient, we can use Stabilization Exercise and william flexion exercise at basic therapy. Objective: The purpose of this research is to declare that giving the stabilization exercise on micro wave diathermy basic therapy more effective in decreasing pain than William flexion exercise on micro wave diathermy basic therapy in spondyloarhtrosis lumbal patient. Method: This research was a true experimental, randomized pre and post test two group design in March to April 2016. From 24 samples of 40-60 years old spondyloarthtrosis lumbal patient in RSUD Dr.H..Kumpulan Pane Tebing Tinggi based in the inclusion criteria, were divided to two groups and get randomly treatment. Group I with stabilization exercise after micro wave diathermy basic therapy and group II with William Flexion Exercise after micro wave diathermy basic therapy. Training conducted over six weeks, 3 times per week and 3 times repetition on each training section. Before and after 6 weeks training, all of the sample measured the pain score using Visual Analog scale. Result: The analysis result show that the decreasing pain score that happened on group I, the initial value 52,50 and final value 20,83 with difference value 31,67 and significantly difference (p <0,05) and decreasing pain score value on group II, the initial value 52,50 and the final value 29,17 with difference value 23,33 in significantly (p <0,05). It means on group I and group II got a significantly decreased of pain. Based on Mann Whitney Test, the average comparison of the decreasing pain after the treatment on both group significantly difference (p <0,05). Conclusion: The conclusion from this research is that stabilization on basic therapy micro wave diathermy is more effective to decrease pain than william flexion exercise on basic micro wave diathermy on spondyloarthrosis lumbal patient.